From elementary to university students’ ıdeas about causes of the seasons - Bostan Sarıoğlan, Ayberk; Küçüközer, Hüseyin (Journal of Turkish Science Education, 2015)
This research was a cross-age study that sought to determine and compare students’ ideas about the causes of the seasons. Toward this aim, the research was carried out with 974 students at different educational levels and across the various age groups. First, the data obtained from the responses to the open-ended question was categorized according to a rubric formulated in line with the goal of the study. The methodology used in analyzing the data derived from the interviews was a grouped categorization of those responses that were construed as having similar intended meanings. Statistically, a significant difference was found between the groups of university students aged 20-22 and the other groups of students who were between the ages of 10-19. In addition, whereas the frequency of encountering some misconceptions decreased with age, on the other hand, the frequency of other misconceptions showed an increase in older students. At the same time, there were some misconceptions which did not vary significantly in frequency across the age groups and still others that did show changes.